Ohjelmistokehitysprojektien ammattilaisten näkemyksiä koronaviruspandemian aikaisesta projektinhallinnasta - Karppinen, Paavo Aapeli (2024)
Based on previous research, software development projects have been challenging for years. From the project management areas, schedule, communication and requirements management have been challenging. Agile methodologies are nowadays extremely popular in software development projects, which means that documentation management has become an issue as well. Remote work has increased due to to the COVID-19 pandemic, which has brought its own set of issues to project management. So that projects can be successfully completed, we need to know where the challenges lie. The goal of this research was to find out the challenges and successes of projects done during the pandemic. The methodologies, both traditional and agile, used in projects have been examined in the theory part of the research. In the theory portion, previous research on project management challenges using Scrum and in general sense were presented. A research gap on the software development project management during the COVID-19 pandemic was discovered during the literature review. Research on the pandemic's effect have been made more on the point of view of the developers and how it affected them. The empirical study was performed as survey research. The target group for the study were people who worked on software development projects during the COVID-19 pandemic. The survey observed the topic qualitatively and quantitatively i.e. the survey had both scaled questions and open-ended questions. The survey received 13 responses in total. Due to the low respondence, the research focused on qualitative analysis and the quantitative data was not deeply processed. The research results indicate that the challenges during the pandemic were similar as to shown in previous research.